Informing learning design with learning analytics to improve teacher inquiry. (15th October 2014) - Persico, Donatella; Pozzi, Francesca
Abstract: This paper proposes an analysis of current research in learning design (LD), a field aiming to improve the quality of educational interventions by supporting their design and fostering the sharing and reuse of innovative practices among educators. This research area, at the moment, focuses on three main strands: the representations that can be used as a common language to communicate about pedagogical plans and other half‐fabricates of the design process, the methodological approaches to LD and the tools that support the LD process. For each of the three strands, the current landscape is discussed, pointing at open issues and indicating future research perspectives, with particular attention to the contribution that learning analytics can make to transform LD from a craft, based on experience, intuition and tacit knowledge, into a mature research area, grounded on data concerning the learning process and hence supporting enquiry while teachers design, run and evaluate the learning process.